Impact of the national health guidance intervention for obesity and cardiovascular risks on healthcare utilisation and healthcare spending in working-age Japanese cohort: regression discontinuity design - Yusuke Tsugawa; Shingo Fukuma; Mitsuru Mukaigawara; Toshiaki Iizuka (BMJ Open)
Objectives Increases in obesity and cardiovascular diseases contribute to rapidly growing healthcare expenditures in many countries. However, little is known about whether the population-level health guidance intervention for obesity and cardiovascular risk factors is associated with reduced healthcare utilisation and spending. The aim of this study was to investigate the effect of population-level health guidance intervention introduced nationally in Japan on healthcare utilisation and spending.Design Retrospective cohort study, using a quasiexperimental regression discontinuity design.Setting Japan’s nationwide employment-based health insurers.Participants Participants in the national health screening programme (from January 2014 to December 2014) aged 40–74 years.Predictors Assignment to health guidance intervention (counselling on healthy lifestyles, and referral to physicians as needed) determined primarily on whether the individual’s waist circumference was above or below the cut-off value in addition to having at least one cardiovascular risk factor.Primary and secondary outcome measures Healthcare utilisation (the number of outpatient visits days, any medication use and any hospitalisation use) and spending (total medical expenditure, outpatient medical expenditure and inpatient medical expenditure) within 3 years of the intervention.Results A total of 51 213 individuals within the bandwidth (±6 cm of waist circumference from the cut-off) out of 113 302 screening participants (median age 50.0 years, 11.9% woman) were analysed. We found that the assignment to the national health guidance intervention was associated with fewer outpatient visit days (−1.3 days; 95% CI, −11.4 to −0.5 days; p=0.03). We found no evidence that the assignment to the health guidance intervention was associated with changes in medication or hospitalisation use, or healthcare spending.Conclusion Among working-age, male-focused Japanese from a health insurer of companies of civil engineering and construction, the national health guidance intervention might be associated with a decline in outpatient visits, with no change in medication/hospitalisation use or healthcare spending.